Measuring child functioning:the Unicef/ Washington Group Module - Mitchell Loeb; Claudia Cappa; Roberta Crialesi; Elena De Palma (Instituto Nacional de Salud Pública, 2017)
The Convention on the Rights of the Child, adopted in 1989 included the first explicit provision relating to the rights of children with disabilities. It included a prohibition against discrimination on the grounds of disability (art. 2), and obligations to provide services for children with disabilities, in order to enable them to achieve the fullest possible social integration (art.23)...